Basilectal Variations and Their Function among Indonesian K-Pop Fans on X - Pratiwi, Aulia Rachma; Andriani, Merry (Lingua Cultura, 2026)
This study examines the basilectal variation and its functions among Indonesian K-pop fans, specifically NCTZen (NCT Fans), on social media X (formerly Twitter). Drawing on the post-creole continuum concept popularized by Bickerton (1975), which conceptualizes basilect as the least prestigious linguistic variety compared to acrolect and mesolect. The variety of languages in this community has grown through digital interactions, reflecting the dynamics of language and users' creativity. A descriptive qualitative method was employed, with data collected from tweets using the hashtag #NEOCITY_THE_MOMENTUM_IN_JAKARTA during NCT 127's concert in Jakarta, Indonesia. Even though the data are drawn from a single fandom, this community reflects a characteristic of Indonesian K-pop fans: intensive online interaction, strong emotional expression, and engagement with transnational culture. The data were filtered to include non-formal linguistic expressions categorized as basilectal, such as colloquial pronouns, non-standard lexicon, phonological simplifications, code-mixing, and hybrid language forms. The findings indicate that basilectal variation is not merely a deviation from standard Indonesian but rather a deliberate linguistic practice that fulfills multiple functions, such as expressing strong affective responses, fostering solidarity, and negotiating transnational fandom belonging. This study contributes to digital sociolinguistics by showing that basilectal forms carry significant symbolic value within online fandom culture. These practices not only challenge the prestige hierarchy of standard language but also highlight the role of creativity, identity expression, and cultural hybridity in digital interactions.